2008
DOI: 10.1007/s00277-008-0469-9
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of occult hepatitis B virus infection in patients with B cell non-Hodgkin’s lymphoma

Abstract: Several reports recently found that patients with B cell non-Hodgkin's lymphoma (NHL) had a higher carrier rate of hepatitis B surface antigen (HBsAg). The current study aimed to examine the hepatitis B virus (HBV) infection status of NHL patients in Taiwan, an HBV-endemic area. Serum HBV and serum hepatitis C virus were measured in 471 NHL patients and 1,013 non-lymphoma cancer patients enrolled between February 2000 and March 2007. Furthermore, nested polymerase chain reaction of HBV-DNA was used to examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
101
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(110 citation statements)
references
References 31 publications
8
101
1
Order By: Relevance
“…Testing of HBV surface antigen alone may in fact underestimate the true prevalence of chronic HBV infection in lymphoma patients. Indeed, a study from Taiwan 20 examining the sera of HBsAg-negative patients with B-cell non-Hodgkin lymphoma (NHL) and nonlymphoma solid tumors and healthy volunteers for the presence of HBV DNA found a statistically higher incidence of occult HBV infection in HBsAg-negative patients with B-cell NHL compared with others. Taken together, these data suggest a potential epidemiologic association between HBV and the development of malignant lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Testing of HBV surface antigen alone may in fact underestimate the true prevalence of chronic HBV infection in lymphoma patients. Indeed, a study from Taiwan 20 examining the sera of HBsAg-negative patients with B-cell non-Hodgkin lymphoma (NHL) and nonlymphoma solid tumors and healthy volunteers for the presence of HBV DNA found a statistically higher incidence of occult HBV infection in HBsAg-negative patients with B-cell NHL compared with others. Taken together, these data suggest a potential epidemiologic association between HBV and the development of malignant lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports examining HBV-DNA in serum have shown that occult HBV infection further adds to the associations of HBsAgpositive HBV infection with NHL and chronic lymphocytic leukemia. [30][31][32] It is also possible that some persons can be positive for HBV-DNA in hepatocytes or lymphocytes or both but negative in serum, which would further affect the association between HBV infection and NHL. …”
mentioning
confidence: 99%
“…What is remarkable in our series is that 38.8% of HBV carriers were co-infected with HCV. Since HCV and HBV carriers are supposed to be more prone to the development of lymphoproliferative diseases [7], it should not be ruled out that a double viral infection determines an even greater risk of lymphoma occurrence [8].…”
Section: Letter To the Editormentioning
confidence: 99%